Green Campus Initiatives as a Branding Tool: A Marketing Study of Indian Private Universities (International Journal of Environmental Sciences, 2025)
Recently, how a college or university fosters sustainability has started to play a major role in its branding efforts. The study examines how green campus practices influence the way people view private universities in India. As more people become aware of environmental problems, educational facilities are choosing eco-friendly approaches which can be found in their buildings and learning programs, how they reuse or recycle waste and their ability to be green-certified. It investigates the effects of these initiatives on how people view the credibility, responsibility and strong academic performance of a university. The study uses both surveys and in-depth interviews of marketing experts from a number of private universities in India. It is clear that environmental activities on campuses support better operations, help with marketing, attract students focused on the environment and give those institutions a lasting advantage over their competition. In conclusion, the study recommends incorporating sustainability into university branding processes to form a reliable and ethical reputation for the institute.